2022
DOI: 10.2174/0929867328666210825110421
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant: A Unique Biomaterial with Life-saving Therapeutic Applications

Abstract: : Pulmonary surfactant is a complex lipoprotein mixture secreted into the alveolar lumen by type 2 pneumocytes, which is composed by tens of different lipids (approximately 90% of its entire mass) and surfactant proteins (approximately 10% of the mass). It is crucially involved in maintaining lung homeostasis by reducing the values of alveolar liquid surface tension close to zero at end-expiration, thereby avoiding the alveolar collapse, and assembling a chemical and physical barrier against inhaled pathogens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 499 publications
0
9
0
Order By: Relevance
“…Alveolar surfactants play a role in reducing alveolar surface tension and maintaining lung compliance ( 78 ). The membrane tension generated by alveolar swelling activates Piezo1 in alveolar type I epithelial cells (AT I), and the Piezo1-mediated rise in Ca 2+ activates pannexin hemichannels and leads to ATP release.…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…Alveolar surfactants play a role in reducing alveolar surface tension and maintaining lung compliance ( 78 ). The membrane tension generated by alveolar swelling activates Piezo1 in alveolar type I epithelial cells (AT I), and the Piezo1-mediated rise in Ca 2+ activates pannexin hemichannels and leads to ATP release.…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…PS is a lipoprotein complex that lines the alveoli and decreases the surface tension to prevent lung atelectasis, and plays an important role in maintaining normal pulmonary function. The endogenous PS deficiency contributes to the lung dysfunction associated with ALI/ARDS [ 25 ]. A large number of in vitro data and in vivo animal studies have demonstrated that PS not only maintains bronchiolar patency during biophysical functions, but also protects of the lungs from the injury and infection of inhaled particles and microorganisms [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, progress in the understanding of surfactant function and dysfunction and our understanding of disease development and progression will improve targeted exogenous surfactant approaches. Second, improved surfactant nebulization methods developed in recent years will allow for early and less-invasive application, before ARDS is fully established. ,, This would have the potential to curtail the progress of multiorgan injury, the major cause of mortality, on an individualized basis. Third, the development of more synthetic preparations can be optimized for specific applications such as delivering other therapeutics such as anti-inflammatory agents on an individualized basis. ,, …”
Section: What Do Physiological and Pathophysiological Studies Teach U...mentioning
confidence: 99%
“…615−617 such as anti-inflammatory agents on an individualized basis. 66,520,618 8.2.5. Surfactant Composition across Mammalian Species.…”
Section: 541mentioning
confidence: 99%